2014
DOI: 10.1021/ef4024349
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Cracking Reaction of Tar over Biomass Char, Using Naphthalene as Model Biomass Tar

Abstract: The tar problems are the major limit for development of biomass gasification. Biomass char has been proven to be an economical and effective catalyst of tar destruction for both utilizations inside the gasifier and in downstream processes after the gasifier. In order to investigate the mechanism of catalytic cracking of tar over a biomass char bed, experimental research was performed in a bench-scale tube flow reactor, choosing rice straw char as the catalyst bed, naphthalene as the model tar compound, and arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…CH 4 reacting in a N 2 atmosphere rapidly deactivated the carbon catalyst, probably because of the pores closure due to carbon deposition. In agreement with results from other studies ( [37][38][39]), the presence of CO 2 or H 2 O was found to prevent the pores blocking and to maintain the char catalytic activity.…”
Section: High Temperature Chemistry Of Alkanes As Tar Model Compoundssupporting
confidence: 92%
See 1 more Smart Citation
“…CH 4 reacting in a N 2 atmosphere rapidly deactivated the carbon catalyst, probably because of the pores closure due to carbon deposition. In agreement with results from other studies ( [37][38][39]), the presence of CO 2 or H 2 O was found to prevent the pores blocking and to maintain the char catalytic activity.…”
Section: High Temperature Chemistry Of Alkanes As Tar Model Compoundssupporting
confidence: 92%
“…Zhang et al [39]. compared the heterogeneous cracking of naphthalene over char with homogeneous decomposition in inert atmosphere.…”
mentioning
confidence: 99%
“…42 The destruction of tar using certain chars as catalysts has proven to be effective. [43][44][45][46][47][48][49] In particular, biochar derived from wood and corn stover were used as catalysts to increase py-gas yield. 44,50,51 Research on the catalytic effect of wastewater biosolids-derived biochar (WB-biochar) during wastewater biosolids pyrolysis is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Results, obtained by the UV-Vis method, overestimate the fractional yield due to an overestimated outlet concentration of benzene. Assuming that the decomposition of naphthalene can form benzene as well [52], an overall fractional yield Φ Benz/T ol+Naph of benzene from toluene and naphthalene can be defined as in eq. (7).…”
Section: Model Gasmentioning
confidence: 99%